PERBANDINGAN PENGANGKATAN ANAK DALAM SISTIM HUKUM PERDATA YANG BERLAKU DI INDONESIA - Aminah, Aminah (Fakultas Hukum, Universitas Diponegoro, 2018)
Indonesia applies various civil law systems, so adoption can use one of the applicable legal systems. This study examines the problem of the civil law system that applies in Indonesia and the comparison of adoption according to the civil law system in Indonesia. Using a normative comparative approach, descriptive research, secondary data and qualitative analysis. The results of the study show that there are 4 Indonesian civil law systems, namely the Western Civil Code using the provisions of the Civil Code, customary law uses the provisions of each customary law, Islamic law uses compilation of Islamic law, and national law by using laws that have been made by Parliament with the government. adoption is known in customary law and national law and has legal consequences both on the legal relationship between both, the right to alimentation and inheritance rights, but in Islamic law adoption does not cause legal consequences at all so it does not inherit each other and there is no legal relationship between the two, and is entitled for wasiat wajibah, while the Civil Code is not known for adoption of children Keywords: Adoption, Indonesian civil law system